Energizing management through innovation and entrepreneurship [electronic resource] : European research and practice - Terziovski, Mile (Routledge studies in innovation, organization and technology, 2009)
This book provides an in-depth understanding of key variables that play a significant role at the various stages of the innovation process, leading to successful commercialisation of products and services.